Notes on the biology of the genus Thalassina (Decapoda Thalassinidae) in mangrove areas of Taft, Eastern Samar - Cemanes, Maria Shiela S. (2017)
Mud lobsters belonging to the genus Thalassina are important members of the mangrove ecosystem, however, not much is known about these organisms. They usually inhabit mangrove ecosystems in littoral and sub-littoral sediments. They are not easily seen but the huge mounds in mangrove areas indicate their presence. This study was conducted in four consecutive weeks of April 2017 and aimed to provide basic biological information on Thalassina spp. in the mangrove areas of Taft, Eastern Samar. Biology of the specimen was analysed focusing on their identification, length-weight relationship, size class frequency, reproductive phases and sex ratio. Set number of specimens were collected from three sampling stations established within the area which were visited weekly. A 100-m transect line per sampling station was laid perpendicular to the shore. Three 20 x 20 m quadrats were established along the line with a 20 m gap in between. Sampling was done at different points within the quadrats as determined by the presence of mounds. A total of 30 individuals per sampling stations were collected and a single species was identified namely Thalassina anomala. For reproductive development, about 92.2% of the dissected specimens had gonads. The reproductive stage, for both the female and male, with the greatest frequency is in ripening and maturing stage that constituted 29.09% and 60.71%, respectively. The frequency of the size class of female is higher and more diverse than males. And lastly, sex ratio of the specimen per station indicates that females were more dominant than males.